Imigrantes espanhóis e poloneses como agentes de relações transnacionais entre a Europa e o sul do Brasil - Regina Weber (Les Cahiers ALHIM)
This article presents actions of individuals and entities belonging to two immigrant groups, during the twentieth century, materialized either in productive activities and artisanal techniques, or in emigrant organizations. The locus of the presence of the Spanish and Polish immigrants is the Southern Region of Brazil, formed by the states of Rio Grande do Sul, Santa Catarina and Paraná, particularly in the first one. Knowledge, cultural representations and political ideas circulated throughout Europe and America, with the mediation of agents, whether these linked to professional practices or those who acted as “ethnic intellectuals”, secular or religious, interested in maintaining an origin identity of the groups which they propose to represent.